Polyolefin resin composition and preparation method thereof, polyolefin foamed beads and polyolefin molded body
By adding Janus sheets to the polyolefin resin and adopting a press-press foaming process, the challenges of polyolefin foaming materials in the prior art in improving compression strength and mechanical properties are solved, and polyolefin foamed beads with lower zero shear viscosity and higher cell density are achieved, thereby improving the multiple properties of the molded body.
Patent Information
- Application Number
- CN202311077048.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-24
AI Technical Summary
Existing polyolefin foaming materials have challenges in improving compressive strength and mechanical properties, especially how to reduce the zero shear viscosity of the polyolefin matrix resin while maintaining or improving foaming properties, thereby affecting the cell structure and material properties.
By adding Janus sheets to the polyolefin resin, a polyolefin resin composition is formed, and polyolefin foamed beads are prepared by using a press-pressure foaming process. The unique properties of Janus sheets allow it to accumulate on the sections of the hole wall, enhancing the support capacity of the bubble cells, thereby improving the tensile, compression and insulation properties of the foamed beads.
The lower zero shear viscosity of polyolefin foamed beads is achieved, the cell density and closed cell rate are improved, the tensile, compression and thermal insulation properties of the molded body are enhanced, while maintaining the original foaming and physical properties.
Smart Images

Figure CN119505425A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polyolefin resin composition and a preparation method thereof, a polyolefin foaming bead and a polyolefin molded body. Background Art
[0002] Polyolefin foam materials have many advantages, such as light weight, high strength, heat resistance, corrosion resistance, thermal insulation, shock absorption, reusability, open and closed porosity can be adjusted according to the application, and the production process and raw materials are green and environmentally friendly. The biggest advantage of the application of kettle-pressed foamed polyolefin beads (EPO beads) is its free formability. The uniform size and stable foaming ratio of EPO beads make them very suitable for molding. Products with complex geometric structures and high-dimensional dimensional accuracy can be produced, and they are mostly used in the high-end market.
[0003] In practical applications, downstream parts manufacturers and OEMs are most concerned about the cushioning performance of polyolefin foam beads and their molded products, which is often characterized by the compressive strength of the foamed materials. Many organizations have carried out work to improve the mechanical properties of polyolefin foam beads and molded products, such as compressive strength.
[0004] The autoclave foaming process is to impregnate the carbon dioxide foaming agent into the molten / semi-molten polyolefin microparticles. As the pressure increases and the impregnation time increases, the carbon dioxide is dispersed in the melt to form a "homogeneous system". When the pressure is quickly released and the material is discharged, the pressure drop causes the carbon dioxide to undergo a phase transition and volume expansion, thereby obtaining autoclave foamed beads with a full appearance and uniform and fine internal pores. The pore density, size, wall thickness, uniformity, open and closed porosity, and foaming ratio of polyolefin foam materials determine the stress distribution and force mode of the pore and pore wall connection structure on the material, thereby determining the macroscopic properties of the material. Controlling the pore structure is a key factor in ensuring the performance of foamed polypropylene.
[0005] At the same time, the rheological properties of the polyolefin matrix resin are also very important for its foaming ability. The ideal matrix resin should have sufficient fluidity to ensure the rapid generation and growth of bubbles during the above foaming process, but often the means of improving the fluidity of the resin will also weaken the foaming performance and physical properties of the resin. Usually, the fluidity of the matrix resin can be characterized by its zero shear viscosity η0. The lower the η0 at a certain temperature, the better its fluidity at that temperature.
[0006] In order to improve the foaming ability of the polyolefin matrix resin and the physical properties of the polyolefin foamed beads, attempts are made to introduce inorganic additives / fillers. However, when the amount added is small, it has no effect on the matrix resin and the foamed beads. When the amount added is large, the fluidity of the matrix resin is reduced (thickening) and the pore structure of the foamed beads is destroyed, which in turn has a negative impact on the foaming ability of the polyolefin matrix resin and the physical properties of the polyolefin foamed beads.
[0007] The 1991 Nobel Prize winner in Physics, de Gennes, proposed the concept of Janus particles, which refers to nanoparticles with different chemical compositions and functions in spatial partitions. Since Janus particles have both polar (hydrophilic) and non-polar (hydrophobic) surfaces, they can be assembled in a direction at the interface of polar / non-polar (water / oil) phases. Among the many morphologies of Janus particles, Janus sheets, as a two-dimensional material, have unique interfacial behaviors determined by their topological morphology. When the flake (or disk-shaped) Janus particles are fixed at the interface of the Pickering emulsion, the interface flipping of the flake particles caused by thermal motion is limited, so the flake Janus particles can stabilize the interface more efficiently. Summary of the invention
[0008] In view of the above-mentioned problems existing in the prior art, the object of the present invention is to provide a polyolefin resin composition and a preparation method thereof, polyolefin foam beads and a polyolefin molded body. By adding Janus sheets, a polyolefin composition with a lower zero shear viscosity than before modification is obtained, and the polyolefin composition is used as a raw material for autoclave foaming. The obtained polyolefin foam beads have an excellent pore structure, and the accumulation of Janus sheets can be observed on the cross-section of the pore wall, which plays a supporting and reinforcing role on the pores. Therefore, the molded body of the above-mentioned foam beads has excellent tensile properties, compression properties and thermal insulation properties.
[0009] The first aspect of the present invention provides a polyolefin resin composition, which comprises a polyolefin, a Janus sheet and an optional functional additive, wherein the thickness of the Janus sheet is ≤200nm and the side length of the cross section is 100nm-2000nm;
[0010] Based on 100 parts by weight of the polyolefin, the content of the Janus sheet is 0.008 to 0.1 parts by weight, and the content of the functional additive is 0 to 1 part by weight.
[0011] The second aspect of the present invention provides a method for preparing the polyolefin resin composition, which comprises: mixing polyolefin, Janus sheet and optional functional additives, extruding strands and cutting to obtain microparticles of the composition.
[0012] The third aspect of the present invention provides a polyolefin foamed bead, which is prepared from the above-mentioned polyolefin resin composition through a kettle pressure foaming process.
[0013] The fourth aspect of the present invention provides a polyolefin molded body, which is obtained by molding the above-mentioned polyolefin foamed beads.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] 1. The polyolefin composition provided by the present invention has a lower η0 at the autoclave foaming process temperature compared with the base polyolefin and the polyolefin composition added with other inorganic fillers, while still maintaining the original foaming performance and physical properties.
[0016] 2. The polyolefin foamed beads provided by the present invention have higher closed cell rate and cell density than the foamed beads prepared from base polyolefin, and obvious Janus particle aggregation can be observed on the cell wall section.
[0017] 3. The polyolefin foamed beads provided by the present invention have higher tensile properties, compression properties and thermal insulation properties than those of foamed beads prepared from base polyolefins.
[0018] 4. The preparation process of the polyolefin composition, foamed beads and molded body used in the present invention is simple and easy to operate, and the requirements for production equipment and operator training are not significantly higher than those of existing process methods.
[0019] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 η* comparison curves of the polyolefin compositions obtained in Example 1, Comparative Example 1 and Comparative Example 3.
[0021] Figure 2 This is a photograph of the cell morphology of the foamed beads obtained in Example 1.
[0022] Figure 3 This is a photo of the cell morphology of the expanded beads obtained in Comparative Example 1.
[0023] Figure 4 This is a photograph of the pore morphology of the expanded beads obtained in Comparative Example 3.
[0024] Figure 5 This is a photograph of the cell wall cross-section of the foamed beads obtained in Example 1.
[0025] Figure 6 This is a photograph of the cell wall cross-section of the foamed beads obtained in Comparative Example 1.
[0026] Figure 7 This is a photograph of the cell wall cross-section of the foamed beads obtained in Comparative Example 3. DETAILED DESCRIPTION
[0027] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0028] According to a first aspect of the present invention, the present invention provides a polyolefin resin composition, the composition comprising a polyolefin, a Janus sheet and an optional functional additive, wherein the thickness of the Janus sheet is ≤200nm, and the side length of the cross section is 100nm-2000nm;
[0029] Based on 100 parts by weight of the polyolefin, the content of the Janus sheet is 0.008 to 0.1 parts by weight, and the content of the functional additive is 0 to 1 part by weight.
[0030] In the present invention, the Janus sheet can be a nano-scale sheet material containing polar groups and non-polar groups on both sides, and any amphiphilic nano-sheet material in the prior art can be used. Preferably, the Janus sheet is a silicon dioxide nanosheet containing polar amino groups and non-polar maleimide groups on both sides, or a silicon dioxide nanosheet containing polar epoxy groups and non-polar alkane groups on both sides. The Janus sheet can be obtained by a variety of preparation methods such as paraffin protection method, Pickering emulsion method, block copolymer assembly-disassembly method, etc. The specific preparation process is known to those skilled in the art and will not be described in detail here.
[0031] Preferably, the thickness of the Janus sheet is ≤100 nm, and the side length of the cross section is 200 nm-1000 nm.
[0032] In the present invention, the polyolefin can be selected from various polyolefins conventionally used in the art, specifically, at least one selected from polypropylene, propylene copolymers (such as terpolymer polypropylene), polyethylene, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-acrylate copolymers, polyvinyl chloride, poly-1-butene, poly-4-methyl-1-pentene and cycloolefin polymers.
[0033] According to the present invention, the functional additive can be various functional additives commonly used in the art, for example, it can be selected from at least one of antioxidants, ultraviolet absorbers, antistatic agents, flame retardants, metal deactivators, pigments, nucleating agents, foam control agents, fillers, stabilizers, reinforcing agents and lubricants.
[0034] In the present invention, the antioxidant may be any antioxidant conventionally used in the art. Preferably, the antioxidant is a hindered phenol antioxidant and a phosphite antioxidant mixed in a mass ratio of 1-5:5-1. The hindered phenol antioxidant may be selected from antioxidant 1010, antioxidant 1076, antioxidant 245 or antioxidant 246; the phosphite antioxidant may be selected from triphenyl phosphate, trimethyl phosphate or antioxidant 168.
[0035] Preferably, based on 100 parts by weight of the polyolefin, the content of the Janus sheet is 0.02-0.06 parts by weight, and the content of the functional additive is 0-0.5 parts by weight.
[0036] The polyolefin composition of the present invention has no significant change in physical properties compared with unmodified polyolefin resin (melting point ±0.2°C, melt index, flexural modulus, and simply supported beam impact strength ±0.4%), and η0 is reduced by 20%, preferably by 30%, where η0 is η0 at the foaming process temperature.
[0037] According to a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned polyolefin resin composition, the preparation method comprising: mixing polyolefin, Janus sheet and optional functional additives, extruding wires and cutting to obtain composite microparticles.
[0038] In the present invention, the mixing of materials can be carried out by various mixing equipment used in the prior art, such as a high-speed mixer, a kneader, etc. Extrusion wire and cutting can be carried out in an extrusion molding machine, through one or more die heads of a twin-screw or single-screw extruder to extrude wire and cut to obtain, and the feeding speed and the pelletizing speed are adjusted to control the particle size and aspect ratio of the particles, and the die head temperature can be selected as needed. These are all conventional selections that can be made by those skilled in the art with reference to the prior art, and will not be repeated here.
[0039] According to the present invention, the cutting of the composition microparticles can be carried out using an underwater microparticle cutting system. Specifically, the microparticle cutting can be carried out in water below 70°C, preferably below 65°C, and more preferably in 45-55°C. In order to be more conducive to EPP foaming and molding, the length / diameter ratio of the composition microparticles can be 0.5-2.0, preferably 0.8-1.3, more preferably 0.9-1.1, and the average weight is 0.1-20 mg, preferably 0.2-10 mg, more preferably 1-3 mg. The average weight is the average value of 200 microparticles selected at random.
[0040] According to a third aspect of the present invention, the present invention provides a polyolefin foamed bead, which is prepared by subjecting the above-mentioned polyolefin resin composition to an autoclave foaming process.
[0041] The microparticles are foamed using a kettle pressure foaming process, which requires dispersing media, surfactants, dispersants, dispersion enhancers and other additives, which are all known to those skilled in the art.
[0042] The specific steps of foaming beads can be as follows:
[0043] 1. In an autoclave foaming device, add the polyolefin composition microparticles and the dispersing medium, surfactant, dispersant, dispersion enhancer and other additives at one time. Stir and mix the dispersion in the autoclave. The stirring speed is 50 to 300 rpm, preferably 150 to 250 rpm.
[0044] 2. Use a physical foaming agent to discharge the residual air in the reactor, feed the foaming agent into the autoclave after sealing it, and heat the temperature in the autoclave to the foaming process temperature after preliminarily adjusting the pressure. The process temperature is ±10°C of the melting point of polypropylene microparticles, preferably ±5°C. Then adjust the pressure in the autoclave to the foaming process pressure, which is 0.5-16MPa, preferably 2-8MPa. Stir continuously for 0.1-2 hours, preferably 0.3-1 hour, under the foaming temperature and pressure conditions.
[0045] 3. Then, the discharge port of the autoclave is opened to discharge the material in the autoclave into the collection tank to obtain foamed beads. While discharging the material, compressed gas is fed to supplement the pressure so that the pressure in the autoclave is kept near the foaming pressure before all the particles are completely foamed and enter the collection tank.
[0046] Wherein, the physical foaming agent can be an organic physical foaming agent or an inorganic physical foaming agent. Organic physical foaming agents include but are not limited to aliphatic hydrocarbons such as propane, butane, pentane, hexane and heptane, alicyclic hydrocarbons such as cyclobutane and cyclohexane, and halogenated hydrocarbons such as chlorofluoromethane, trifluoromethane, 1,2-difluoroethane, 1,2,2,2-tetrafluoroethane, methyl chloride, ethyl chloride and dichloromethane. The inorganic physical foaming agent includes but is not limited to at least one of air, nitrogen, carbon dioxide, oxygen and water. Supercritical carbon dioxide, supercritical nitrogen or a mixture of any proportion thereof.
[0047] The apparent density of the kettle-pressed foamed beads conventionally selected in the art may include but is not limited to 10-200 g / L, preferably 15-180 g / L. Those skilled in the art are aware of this and will not be elaborated herein.
[0048] Under the same process conditions, the autoclave foamed beads prepared from the polyolefin composition of the present invention can reduce the apparent density by 10%, preferably by 20%, compared with the beads prepared from unmodified polyolefin under the same process conditions. Under the same apparent density, the closed cell rate can be increased by 8%, preferably by 12%, and the average cell diameter can be reduced by 20%, preferably by 30%.
[0049] According to a fourth aspect of the present invention, there is provided a polyolefin molded body, which is obtained by molding the above-mentioned polyolefin foamed beads.
[0050] The specific foaming molding process conditions can be conventionally selected in the art. The specific process is known to those skilled in the art and will not be described in detail here.
[0051] The apparent density of the conventional foamed molded body in the art may include but is not limited to 10-200 g / L, preferably 15-180 g / L. Those skilled in the art are aware of this and will not be elaborated herein.
[0052] Under the same process conditions, the polyolefin foam bead molding of the present invention, compared with the foam molding prepared from unmodified polyolefin, at the same apparent density, the compressive strength (50%) can be increased by ≥30%, preferably by ≥50%; the tensile strength can be increased by ≥30%, preferably by ≥50%; the thermal conductivity can be reduced by 10%, preferably by 15%.
[0053] The substances and parameters not limited in the present invention can be selected according to the existing technology and belong to the conventional technical means in this field.
[0054] The present invention will be further described below with reference to the following examples, but is not limited to these examples.
[0055] In the following examples and comparative examples, the raw materials and instruments used include:
[0056] Kaolin: B&K, ACROS, analytical grade.
[0057] Sodium dodecylbenzenesulfonate: Tianjin Guangfu Fine Chemical Research Institute, analytical grade.
[0058] Aluminum sulfate: Tianjin Guangfu Technology Development Co., Ltd., analytical grade.
[0059] Random terpolymer polypropylene E680E: Melt index is 7.5g / 10min, and η0=1.19×10 at foaming process temperature (145℃) 4 Pa·s, produced by Sinopec Shanghai Petrochemical.
[0060] Random ethylene-propylene copolymer polypropylene B4908: Melt index is 7.5g / 10min, and η0=1.21×10 at foaming process temperature (145℃) 4 Pa·s, produced by Sinopec Yanshan Petrochemical.
[0061] Random propylene-butane copolymer polypropylene M850B: Melt index is 7.5g / 10min, and η0=1.17×10 at foaming process temperature (145℃) 4 Pa·s, produced by Sinopec Shanghai Petrochemical.
[0062] Janus wafers and silicon dioxide wafers are all homemade, and the specific preparation methods are as follows:
[0063] JanusA, JanusB, JanusC, JanusD and JanusE are silica nanosheets containing polar amino groups and non-polar maleimide groups on both sides, respectively. The preparation method is as follows: prepare 1500mL of a 10wt% aqueous solution of hydrolyzed styrene-maleic anhydride copolymer, and then dissolve the solution in 7500mL of water. The pH value of the mixture is adjusted to 2.5 with hydrochloric acid. Then, 1000 grams of n-decane, 1100g of (3-aminopropyl) triethoxysilane, 1240g of 3-(trimethoxysilyl) propyl methacrylate, 5200g of tetraethoxysilane, 10000g of divinylbenzene and 100g of 2,2′-azo (2-methylpropionitrile) solution are added and mixed. The oil mixture is dispersed in the aqueous solution and stirred at a speed of 12000rpm for 5min to form an oil-in-water emulsion. The emulsifier was fixed at the bottom and stirred at 25°C for 7 hours to obtain the process of self-organized interfacial sol-gel silane. Then, the emulsion was heated to 70°C to initiate the polymerization of divinylbenzene on the inner surface. The Janus hollow sphere shell was obtained. It was then crushed into Janus nanosheets using a colloid mill.
[0064] Among the prepared Janus sheets, JanusA: thickness 50nm, cross-sectional side length 750nm; JanusB: thickness 125nm, cross-sectional side length 1500nm; JanusC: thickness 80nm, cross-sectional side length 400nm; JanusD: thickness 250nm, cross-sectional side length 1500nm; JanusE: thickness 180nm, cross-sectional side length 2500nm.
[0065] JanusF and JanusG contain polar epoxy groups and non-polar alkane groups on both sides of the silica nanosheet. The preparation method is as follows: prepare 1500mL of 10wt% hydrolyzed styrene-epoxy resin copolymer aqueous solution, and then dissolve the solution in 7500mL of water. The pH value of the mixture is adjusted to 2.5 with hydrochloric acid. Then add 1000 grams of n-decane, 1100g of triethoxy (tetradecyl) silane, 1240g of 3-(trimethoxymethylsilyl) methyl methacrylate, 5200g of tetraethoxysilane, 10000g of divinylbenzene and 100g of 2,2′-azo (2-methylpropionitrile) solution. The oil mixture is dispersed in the aqueous solution and stirred at a speed of 12000rpm for 5min to form an oil-in-water emulsion. The emulsifier is fixed below and stirred at 25°C for 7h to obtain the process of self-organized interface sol-gel silane. Then, the emulsion is heated to 70°C to initiate polymerization of divinylbenzene on the inner surface, thereby obtaining a Janus hollow sphere shell, which is then crushed into Janus nanosheets using a colloid mill.
[0066] Among the prepared Janus sheets, JanusF has a thickness of 75 nm and a cross-sectional side length of 800 nm; JanusG has a thickness of 300 nm and a cross-sectional side length of 3000 nm.
[0067] The specific preparation method of silica sheet A is as follows: 9000mL of water is adjusted to a pH value of 2.5 using hydrochloric acid solution. Then 1000 grams of n-decane, 5200g of tetraethoxysilane, 10000g of divinylbenzene and 100g of 2,2′-azo (2-methylpropionitrile) solution are added and mixed. The oil mixture is dispersed into the aqueous solution and stirred at a speed of 12000rpm for 5min to form an oil-in-water emulsion. The emulsifier is fixed below and stirred at 25°C for 7h to obtain the process of self-organized interface sol-gel silane. Then, the emulsion is heated to 70°C to induce the polymerization of divinylbenzene on the inner surface. The hollow silica sphere shell is obtained. It is then crushed into silica nanosheets using a colloid mill. Silica sheet A has the same appearance size as JanusA, but does not contain functional groups on both sides.
[0068] The specific preparation method of silica sheet B is as follows: 9000mL of water is adjusted to a pH value of 2.5 using hydrochloric acid solution. Then 1000 grams of n-decane, 1100g (3-aminopropyl) triethoxysilane, 1240g 3-(trimethoxymethylsilyl) propyl methacrylate, 5200g tetraethoxysilane, 10000g divinylbenzene and 100g 2,2′-azo (2-methylpropionitrile) solution are added and mixed. The oil mixture is dispersed into the aqueous solution and stirred at a speed of 12000rpm for 5min to form an oil-in-water emulsion. The emulsifier is fixed below and stirred at 25°C for 7h to obtain a self-organized interface sol-gel silane process. Then, the emulsion is heated to 70°C to initiate the polymerization of divinylbenzene on the inner surface. The hollow silica sphere shell is obtained. It is then crushed into silica nanosheets using a colloid mill. Silica wafer B has the same appearance dimensions as Janus A, but contains amino polar functional groups on both sides;
[0069] The specific preparation method of silica sheet C is as follows: 9000mL of water is adjusted to a pH value of 2.5 using a hydrochloric acid solution. Then 1000 grams of n-decane, 1100g of triethoxy (tetradecyl) silane, 1240g of 3-(trimethoxymethylsilyl) propyl methacrylate, 5200g of tetraethoxysilane, 10000g of divinylbenzene and 100g of 2,2′-azo (2-methylpropionitrile) solution are added and mixed. The oil mixture is dispersed into the aqueous solution and stirred at a speed of 12000rpm for 5min to form an oil-in-water emulsion. The emulsifier is fixed below and stirred at 25°C for 7h to obtain a self-organized interface sol-gel silane process. Then, the emulsion is heated to 70°C to initiate the polymerization of divinylbenzene on the inner surface. The hollow silica sphere shell is obtained. It is then crushed into silica nanosheets using a colloid mill. Silica sheet C has the same apparent dimensions as Janus A, but contains alkane non-polar functional groups on both sides.
[0070] Styrene-maleic anhydride copolymer, AR, J&K reagent.
[0071] Styrene-epoxy copolymer, AR, J&K reagent.
[0072] Hydrochloric acid, AR, J&K reagent.
[0073] n-Decane, AR, J&K reagent.
[0074] (3-Aminopropyl)triethoxysilane, AR, J&K reagent.
[0075] Triethoxy(tetradecyl)silane, AR, J&K reagent.
[0076] 3-(Trimethoxysilyl)propyl methacrylate, AR, J&K reagent.
[0077] Tetraethoxysilane, AR, J&K reagent.
[0078] Divinylbenzene, AR, J&K reagent.
[0079] 2,2′-Azo(2-methylpropionitrile) solution, AR, J&K reagent.
[0080] Underwater pelletizing system: Labline 1000, BKG, Germany.
[0081] Equipment for preparing foamed beads by kettle pressure foaming: COF5-250, Beijing Xindali Company.
[0082] Foamed beads in-mold forming device: EHV-CE-PP 000269 / 2019, Erlenbach, Germany.
[0083] In the following examples and comparative examples, the testing methods of the relevant data are as follows:
[0084] 1. Melt flow rate (MFR): tested according to the method specified in GB / T 3682, where the test temperature is 230°C and the load is 2.16 kg.
[0085] 2. Melting point: Tested according to the method specified in GB / T 28724.
[0086] 3. Flexural modulus of polyolefin composition: tested according to the method specified in GB / T 9341.
[0087] 4. Simply supported beam impact strength of polypropylene composition: tested according to the method specified in GB / T 1943.
[0088] 5. Polyolefin composition η0: When the foam beads are prepared at a temperature of 145°C, a shear rate range of 0.01-100 rad / s, and a strain value of 5%, a rotational rheometer is used to measure the relationship between the apparent viscosity η* and the shear rate w. When η* no longer increases with the shear rate in the low-frequency region, it is the η0 of the polyolefin composition.
[0089] 6. Apparent density of polyolefin foam beads: CPA225D, density accessory YDK01, Satorius, Germany. Test method: Use the density accessory of Satorius balance and the water displacement method to obtain the apparent density of the foam beads.
[0090] 7. Closed-cell rate of polyolefin foam beads: ULTRAFOAM 1200e, Quantachrome Instruments, Inc., USA. Test method: in accordance with GB / T 10799-2008.
[0091] 8. Density test method for foamed products: Measure according to the method described in GB / T 6343.
[0092] 9. Compression strength of foamed material (50%): tested in accordance with the method specified in ISO 844.
[0093] 10. Test method for tensile strength and thermal insulation capacity of foam materials: Thermal conductivity shall be tested according to the method specified in GB / T 10295.
[0094] 11. Test method for average cell diameter of polyolefin foam beads: The foam material is quenched with liquid nitrogen, the cross section is sprayed with gold, and the cell structure inside the foam material is examined using a scanning electron microscope (SEM). 20 cells in the field of view are randomly selected, their cell diameters are measured, and the average value is calculated.
[0095] Example 1
[0096] (1) Preparation of polyolefin composition:
[0097] Based on 100 parts by weight of random terpolymer polypropylene E680E, the addition amount of JanusA is 0.05 parts by weight, the addition amount of antioxidant 1010 is 0.2 parts by weight, and the addition amount of antioxidant 168 is 0.1 parts by weight. Then, the mixture is added to a high-speed stirrer for uniform mixing, and then the mixed material is added to the feeder of a twin-screw extruder, and the material enters the twin screw through the feeder. During the processing, the temperature of the screw is maintained between 160-200°C, and the screw is melt-mixed and uniformly mixed, extruded, and molded at 260°C, and then dried under 50°C water to obtain polyolefin composition microparticles with a length / diameter ratio of 1.0 and an average weight of 2 mg.
[0098] The microparticles of the composition of Test Example 1 have a melting point of 140.3°C, a melt index of 7.1 g / 10 min, a flexural modulus of 766 MPa, and a room temperature simply supported beam impact strength of 6.3 kJ / m 2 . Its η0 is shown in Table 1, and η* is shown in Figure 1 .
[0099] (2) Preparation of polyolefin foam beads:
[0100] 100 parts by weight of the composition microparticles prepared in step 1 and 300 parts by weight of deionized water as a dispersion medium, 0.3 parts by weight of sodium dodecylbenzene sulfonate as a surfactant, 5 parts by weight of kaolin as a dispersant, 0.13 parts by weight of aluminum sulfate as a dispersion enhancer and other auxiliary agents are added to the autoclave pressure foaming device at one time, and the dispersion in the autoclave is mixed at a stirring speed of 80 rpm. 99.99wt% carbon dioxide is used as a foaming agent to discharge the residual air in the reactor, and the foaming agent is fed into the autoclave after sealing the autoclave, and the pressure is initially adjusted to 2.0MPa. Then. Heat it to 145°C at a uniform heating rate. Then, adjust the pressure in the autoclave to 4.0MPa. Under the foaming temperature and pressure conditions, continue stirring for 0.5 hours. Then, the discharge port of the autoclave is opened to discharge the material in the reactor into the collection tank to obtain polyolefin composition foam beads. Dehydrate and dry after collecting the beads.
[0101] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Example 1 are tested. The results are shown in Table 1. The cell morphology and cell wall section are shown in Table 1. Figure 2 , Figure 5 .
[0102] (3) Preparation of polyolefin foamed molded body:
[0103] In a molding machine, the foamed beads prepared above were fed into a molding die and molded at a steam pressure of 2.0 bar for 15 minutes, and then the obtained molded body was aged at a temperature of 100° C. and a pressure of standard atmospheric pressure for 24 hours to obtain a foamed molded body. The apparent density of the molded body was made consistent with the apparent density of the foamed beads through industrial control, and the compression strength, tensile strength and thermal conductivity of the molded body were tested, and the results are shown in Table 1.
[0104] Example 2
[0105] (1) Preparation of polyolefin composition:
[0106] The preparation process is the same as step (1) of Example 1, except that Janus A is replaced by Janus B.
[0107] The microparticles of the composition of Test Example 2 have a melting point of 140.4°C, a melt index of 7.1 g / 10 min, a flexural modulus of 769 MPa, and a room temperature simply supported beam impact strength of 6.2 kJ / m 2 Its η0 is shown in Table 1.
[0108] (2) Preparation of polyolefin foam beads:
[0109] The preparation process is the same as step (2) of Example 1.
[0110] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Example 2 were tested. The results are shown in Table 1.
[0111] (3) Preparation of polyolefin foamed molded body:
[0112] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0113] Example 3
[0114] (1) Preparation of polyolefin composition:
[0115] The preparation process is the same as step (1) of Example 1, except that JanusA is replaced by JanusC.
[0116] The microparticles of the composition of Test Example 3 have a melting point of 140.5°C, a melt index of 7.0 g / 10 min, a flexural modulus of 764 MPa, and a room temperature simply supported beam impact strength of 6.3 kJ / m 2 Its η0 is shown in Table 1.
[0117] (2) Preparation of polyolefin foam beads:
[0118] The preparation process is the same as step (2) of Example 1.
[0119] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Example 3 were tested. The results are shown in Table 1.
[0120] (3) Preparation of polyolefin foamed molded body:
[0121] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0122] Example 4
[0123] (1) Preparation of polyolefin composition:
[0124] The preparation process is the same as step (1) of Example 1, except that JanusA is replaced by JanusF.
[0125] The microparticles of the composition of Test Example 4 have a melting point of 140.6°C, a melt index of 7.2 g / 10 min, a flexural modulus of 762 MPa, and a room temperature simply supported beam impact strength of 6.4 kJ / m 2 Its η0 is shown in Table 1.
[0126] (2) Preparation of polyolefin foam beads:
[0127] The preparation process is the same as step (2) of Example 1.
[0128] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Test Example 4 are shown in Table 1.
[0129] (3) Preparation of polyolefin foamed molded body:
[0130] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0131] Example 5
[0132] (1) Preparation of polyolefin composition:
[0133] The preparation process is the same as step (1) of Example 1, except that 0.05 parts by weight of Janus A is replaced with a composition of 0.02 parts by weight of Janus A, 0.15 parts by weight of Janus B and 0.15 parts by weight of Janus C.
[0134] The microparticles of the composition of Test Example 5 have a melting point of 140.7°C, a melt index of 6.9 g / 10 min, a flexural modulus of 769 MPa, and a room temperature simply supported beam impact strength of 6.3 kJ / m 2 Its η0 is shown in Table 1.
[0135] (2) Preparation of polyolefin foam beads:
[0136] The preparation process is the same as step (2) of Example 1.
[0137] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Test Example 5 are shown in Table 1.
[0138] (3) Preparation of polyolefin foamed molded body:
[0139] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0140] Example 6
[0141] (1) Preparation of polyolefin composition:
[0142] The preparation process is the same as step (1) of Example 1, except that 0.05 parts by weight of Janus A is replaced by 0.09 parts by weight of Janus B.
[0143] The microparticles of the composition of Test Example 6 have a melting point of 140.7°C, a melt index of 6.9 g / 10 min, a flexural modulus of 769 MPa, and a room temperature simply supported beam impact strength of 6.2 kJ / m 2 Its η0 is shown in Table 1.
[0144] (2) Preparation of polyolefin foam beads:
[0145] The preparation process is the same as step (2) of Example 1.
[0146] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Test Example 6 are shown in Table 1.
[0147] (3) Preparation of polyolefin foamed molded body:
[0148] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0149] Example 7
[0150] (1) Preparation of polyolefin composition:
[0151] The preparation process is the same as step (1) of Example 1, except that 0.05 parts by weight of Janus A is replaced by 0.01 parts by weight of Janus B.
[0152] The microparticles of the composition of test example 7 have a melting point of 140.5°C, a melt index of 7.0 g / 10 min, a flexural modulus of 766 MPa, and a room temperature simply supported beam impact strength of 6.3 kJ / m 2 Its η0 is shown in Table 1.
[0153] (2) Preparation of polyolefin foam beads:
[0154] The preparation process is the same as step (2) of Example 1.
[0155] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Test Example 7 are shown in Table 1.
[0156] (3) Preparation of polyolefin foamed molded body:
[0157] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0158] Example 8
[0159] (1) Preparation of polyolefin composition:
[0160] The preparation process is the same as step (1) of Example 1, except that E680E is replaced by B4908.
[0161] The microparticles of the composition of Test Example 8 have a melting point of 140.5°C, a melt index of 7.1 g / 10 min, a flexural modulus of 771 MPa, and a room temperature simply supported beam impact strength of 6.0 kJ / m 2 Its η0 is shown in Table 1.
[0162] (2) Preparation of polyolefin foam beads:
[0163] The preparation process is the same as step (2) of Example 1.
[0164] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Example 8 were tested. The results are shown in Table 1.
[0165] (3) Preparation of polyolefin foamed molded body:
[0166] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0167] Example 9
[0168] (1) Preparation of polyolefin composition:
[0169] The preparation process is the same as step (1) of Example 1, except that E680E is replaced by M850B.
[0170] The microparticles of the composition of Test Example 9 have a melting point of 140.2°C, a melt index of 7.1 g / 10 min, a flexural modulus of 766 MPa, and a room temperature simply supported beam impact strength of 6.2 kJ / m 2 Its η0 is shown in Table 1.
[0171] (2) Preparation of polyolefin foam beads:
[0172] The preparation process is the same as step (2) of Example 1.
[0173] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Test Example 9 are shown in Table 1.
[0174] (3) Preparation of polyolefin foamed molded body:
[0175] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0176] Comparative Example 1
[0177] (1) Preparation of polyolefin composition:
[0178] The preparation process is the same as step (1) of Example 1, except that Janus A is not added.
[0179] The microparticles of the composition of comparative example 1 have a melting point of 140.5°C, a melt index of 7.0 g / 10 min, a flexural modulus of 768 MPa, and a simple impact strength of 6.3 kJ / m 2 , η*see Figure 1 .
[0180] (2) Preparation of polyolefin foam beads:
[0181] The preparation process is the same as step (2) of Example 1, except that the foaming pressure is 5 MPa.
[0182] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Comparative Example 1 were tested. The results are shown in Table 1. The cell morphology and cell wall section are shown in Table 1. Figure 3 , Figure 6 .
[0183] (3) Preparation of polyolefin foamed molded body:
[0184] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0185] Comparative Example 2
[0186] (1) Preparation of polyolefin composition:
[0187] The preparation process is the same as step (1) of Example 1, except that Janus A is replaced with silicon dioxide wafer A.
[0188] The microparticles of the composition of comparative example 2 have a melting point of 140.5°C, a melt index of 7.0 g / 10 min, a flexural modulus of 768 MPa, and a simple impact strength of 6.3 kJ / m 2 .
[0189] (2) Preparation of polyolefin foam beads:
[0190] The preparation process is the same as step (2) of Comparative Example 1.
[0191] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Comparative Example 2 were tested. The results are shown in Table 1.
[0192] (3) Preparation of polyolefin foamed molded body:
[0193] The preparation process is the same as step (3) of comparative example 1. The results of testing the compressive strength, tensile strength and thermal conductivity of the molded body are shown in Table 1.
[0194] Comparative Example 3
[0195] (1) Preparation of polyolefin composition:
[0196] The preparation process is the same as step (1) of Example 1, except that 0.05 parts by weight of Janus A is replaced by 0.15 parts by weight of Janus A.
[0197] The microparticles of the composition of comparative example 3 have a melting point of 140.8°C, a melt index of 6.8 g / 10 min, a flexural modulus of 767 MPa, and a simple impact strength of 6.4 kJ / m 2 , η*see Figure 1 .
[0198] (2) Preparation of polyolefin foam beads:
[0199] The preparation process is the same as step (2) of Comparative Example 1.
[0200] The apparent density, closed cell ratio and average cell diameter of the foamed beads of comparative example 3 were tested. The results are shown in Table 1. The cell morphology and cell wall section are shown in Table 2. Figure 4 , Figure 7 .
[0201] (3) Preparation of polyolefin foamed molded body:
[0202] The preparation process is the same as step (3) of comparative example 1. The results of testing the compressive strength, tensile strength and thermal conductivity of the molded body are shown in Table 1.
[0203] Comparative Example 4
[0204] (1) Preparation of polyolefin composition:
[0205] The preparation process is the same as step (1) of Example 1, except that 0.05 parts by weight of Janus A is replaced by 0.005 parts by weight of Janus A.
[0206] The microparticles of the composition of comparative example 4 have a melting point of 140.5°C, a melt index of 7.0 g / 10 min, a flexural modulus of 768 MPa, and a simple impact strength of 6.3 kJ / m 2 .
[0207] (2) Preparation of polyolefin foam beads:
[0208] The preparation process is the same as step (2) of Comparative Example 1.
[0209] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Comparative Example 4 were tested. The results are shown in Table 1.
[0210] (3) Preparation of polyolefin foamed molded body:
[0211] The preparation process is the same as step (3) of comparative example 1. The results of testing the compressive strength, tensile strength and thermal conductivity of the molded body are shown in Table 1.
[0212] Comparative Example 5
[0213] (1) Preparation of polyolefin composition:
[0214] The preparation process is the same as step (1) of Example 1, except that JanusA is replaced by JanusD.
[0215] The microparticles of the composition of comparative example 5 have a melting point of 140.7°C, a melt index of 6.8 g / 10 min, a flexural modulus of 771 MPa, and a simple impact strength of 6.2 kJ / m 2 .
[0216] (2) Preparation of polyolefin foam beads:
[0217] The preparation process is the same as step (2) of Comparative Example 1.
[0218] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Comparative Example 5 were tested. The results are shown in Table 1.
[0219] (3) Preparation of polyolefin foamed molded body:
[0220] The preparation process is the same as step (3) of comparative example 1. The results of testing the compressive strength, tensile strength and thermal conductivity of the molded body are shown in Table 1.
[0221] Comparative Example 6
[0222] (1) Preparation of polyolefin composition:
[0223] The preparation process is the same as step (1) of Example 1, except that JanusA is replaced by JanusE.
[0224] The microparticles of the composition of comparative example 6 have a melting point of 140.7°C, a melt index of 6.9 g / 10 min, a flexural modulus of 763 MPa, and a simple impact strength of 6.4 kJ / m 2 .
[0225] (2) Preparation of polyolefin foam beads:
[0226] The preparation process is the same as step (2) of Comparative Example 1.
[0227] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Comparative Example 6 were tested. The results are shown in Table 1.
[0228] (3) Preparation of polyolefin foamed molded body:
[0229] The preparation process is the same as step (3) of comparative example 1. The results of testing the compressive strength, tensile strength and thermal conductivity of the molded body are shown in Table 1.
[0230] Comparative Example 7
[0231] (1) Preparation of polyolefin composition:
[0232] The preparation process is the same as step (1) of Example 1, except that JanusA is replaced by JanusG.
[0233] The microparticles of the composition of comparative example 7 have a melting point of 140.7°C, a melt index of 6.9 g / 10 min, a flexural modulus of 771 MPa, and a room temperature simple supported impact strength of 6.3 kJ / m 2 .
[0234] (2) Preparation of polyolefin foam beads:
[0235] The preparation process is the same as step (2) of Comparative Example 1.
[0236] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Comparative Example 7 were tested. The results are shown in Table 1.
[0237] (3) Preparation of polyolefin foamed molded body:
[0238] The preparation process is the same as step (3) of comparative example 1. The results of testing the compressive strength, tensile strength and thermal conductivity of the molded body are shown in Table 1.
[0239] Comparative Example 8
[0240] (1) Preparation of polyolefin composition:
[0241] The preparation process is the same as step (1) of Example 1, except that Janus A is replaced with silicon dioxide wafer B.
[0242] The microparticles of the composition of comparative example 8 have a melting point of 140.5°C, a melt index of 7.0 g / 10 min, a flexural modulus of 768 MPa, and a simple impact strength of 6.3 kJ / m 2 .
[0243] (2) Preparation of polyolefin foam beads:
[0244] The preparation process is the same as step (2) of Comparative Example 1.
[0245] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Comparative Example 8 were tested. The results are shown in Table 1.
[0246] (3) Preparation of polyolefin foamed molded body:
[0247] The preparation process is the same as step (3) of comparative example 1. The results of testing the compressive strength, tensile strength and thermal conductivity of the molded body are shown in Table 1.
[0248] Comparative Example 9
[0249] (1) Preparation of polyolefin composition:
[0250] The preparation process is the same as step (1) of Example 1, except that Janus A is replaced with silicon dioxide wafer C.
[0251] The microparticles of the composition of comparative example 9 have a melting point of 140.5°C, a melt index of 7.0 g / 10 min, a flexural modulus of 768 MPa, and a simple impact strength of 6.3 kJ / m 2 .
[0252] (2) Preparation of polyolefin foam beads:
[0253] The preparation process is the same as step (2) of Comparative Example 1.
[0254] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Comparative Example 9 were tested. The results are shown in Table 1.
[0255] (3) Preparation of polyolefin foamed molded body:
[0256] The preparation process is the same as step (3) of comparative example 1. The results of testing the compressive strength, tensile strength and thermal conductivity of the molded body are shown in Table 1.
[0257] Comparative Example 10
[0258] (1) Preparation of polyolefin composition:
[0259] The preparation process is the same as step (1) of implementation 1, except that 0.05 parts by weight of Janus A is replaced by 3 parts by weight of dihydroxypropyl octadecanoate.
[0260] The microparticles of the composition of comparative example 10 have a melting point of 143.5°C, a melt index of 8.1 g / 10 min, a flexural modulus of 657 MPa, and a simple impact strength of 6.8 kJ / m 2 .
[0261] (2) Preparation of polyolefin foam beads:
[0262] The preparation process is the same as step (2) of Comparative Example 1.
[0263] The apparent density, closed cell ratio and average cell diameter of the foamed beads of Comparative Example 10 were tested. The results are shown in Table 1.
[0264] (3) Preparation of polyolefin foamed molded body:
[0265] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0266] Comparative Example 11
[0267] (1) Preparation of polyolefin composition:
[0268] The preparation process is the same as step (1) of Comparative Example 1.
[0269] The microparticles of the composition of comparative example 11 have a melting point of 140.5°C, a melt index of 7.0 g / 10 min, a flexural modulus of 768 MPa, and a simple impact strength of 6.3 kJ / m 2 .
[0270] (2) Preparation of polyolefin foam beads:
[0271] The preparation process is the same as step (2) of Example 1.
[0272] The apparent density, closed cell ratio and average cell diameter of the foamed beads of comparative example 11 were tested. The results are shown in Table 1.
[0273] (3) Preparation of polyolefin foamed molded body:
[0274] The preparation process is the same as step (3) of Example 1. The compressive strength, tensile strength and thermal conductivity of the molded body are tested and the results are shown in Table 1.
[0275] Table 1
[0276]
[0277]
[0278] From the results of Examples 1-3, Comparative Examples 1, 5-7, and 11, it can be seen that Janus sheets with appropriate size specifications can effectively reduce η0 of the base polyolefin resin and improve the foaming ability of the composition without affecting the various properties of the base resin. The weight reduction performance, pore quality, tensile performance, compression performance, and thermal insulation capacity of the autoclave foamed products are significantly improved. From Comparative Example 10, it can be seen that using other methods to reduce η0 will significantly reduce the foaming performance of the polyolefin composition.
[0279] From the results of Examples 4 and 5 and Comparative Examples 2, 8 and 9, it can be seen that the Janus sheet needs to have functional groups with different polarities on both sides, and the type of functional groups has no significant effect on the viscosity reduction effect, the foaming ability of the composition and the various properties of the foamed product. The silicon dioxide sheet without functional groups on both sides or with functional groups of the same polarity on both sides has no effect on the various properties of the composition and the foamed product.
[0280] It can be seen from the results of Examples 6 and 7 and Comparative Examples 3 and 4 that too high or too low an amount of Janus flakes added will affect the viscosity reduction effect of the polyolefin composition and the effect of improving various properties of the composition foam.
[0281] It can be seen from the results of Comparative Example 10 that the fluidity of the polyolefin composition can be reduced by adding a lubricant such as monoglyceride, but the properties of the polyolefin composition, foamed beads and foamed body will also be greatly weakened.
[0282] from Figure 2-7 It can be seen that the pores of Example 1 are the most regular and fine, no inorganic particles appear in the pores to destroy the pore structure, and a large amount of Janus sheets are observed to accumulate on the cut pore walls.
[0283] No inorganic particles were observed inside the pores or on the pore walls of Comparative Example 1. In contrast, inorganic particle agglomeration was observed inside the pores of Comparative Example 3, but no Janus sheet accumulation was observed on the cut pore walls.
[0284] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A polyolefin resin composition, characterized in that The composition contains polyolefin, Janus sheet and optional functional additives, wherein the thickness of the Janus sheet is ≤200nm and the side length of the cross section is 100nm-2000nm; Based on 100 parts by weight of the polyolefin, the content of the Janus sheet is 0.008 to 0.1 parts by weight, and the content of the functional additive is 0 to 1 part by weight.
2. The polyolefin resin composition according to claim 1, wherein The Janus sheet is a nano-scale sheet material having polar groups and non-polar groups on both sides.
3. The polyolefin resin composition according to claim 2, wherein The Janus sheet is a silicon dioxide nanosheet having polar groups and non-polar groups on both sides; Preferably, the Janus sheet is a silicon dioxide nanosheet having polar amino groups and non-polar maleimide groups on both sides, or a silicon dioxide nanosheet having polar epoxy groups and non-polar alkane groups on both sides.
4. The polyolefin resin composition according to claim 1, wherein The thickness of the Janus sheet is ≤100nm, and the side length of the cross section is 200nm-1000nm.
5. The polyolefin resin composition according to claim 1, wherein The polyolefin is selected from at least one of polypropylene, propylene copolymers, polyethylene, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-acrylate copolymers, polyvinyl chloride, poly-1-butene, poly-4-methyl-1-pentene and cycloolefin polymers.
6. The polyolefin resin composition according to claim 1, wherein The functional additive is selected from at least one of an antioxidant, an ultraviolet absorber, an antistatic agent, a flame retardant, a metal deactivator, a pigment, a nucleating agent, a foam control agent, a filler, a stabilizer, a reinforcing agent and a lubricant; The antioxidant is preferably a hindered phenol antioxidant and a phosphite antioxidant mixed in a mass ratio of 1-5:5-1; wherein the hindered phenol antioxidant is selected from antioxidant 1010, antioxidant 1076, antioxidant 245 or antioxidant 246; and the phosphite antioxidant is selected from triphenyl phosphate, trimethyl phosphate or antioxidant 168.
7. The polyolefin resin composition according to claim 1, wherein Based on 100 parts by weight of the polyolefin, the content of the Janus sheet is 0.02-0.06 parts by weight, and the content of the functional additive is 0-0.5 parts by weight.
8. The method for preparing a polyolefin resin composition according to any one of claims 1 to 7, characterized in that: The preparation method comprises: mixing polyolefin, Janus sheet and optional functional auxiliary agent, extruding wire material and cutting to obtain composite micro particles.
9. A polyolefin foamed bead, characterized in that: The foamed beads are prepared from the polyolefin resin composition according to any one of claims 1 to 7 through a kettle pressure foaming process.
10. A polyolefin molded article, characterized in that: The molded body is obtained by molding the polyolefin expanded beads according to claim 9.
Citation Information
Patent Citations
Polyolefin foaming composition, polyolefin foaming bead, preparation method of polyolefin foaming bead, and foaming bead formed body
CN114058124A
Foamed polyolefin bead and preparation method thereof
CN114456511A
Water-based acrylic coating added with Janus silicon dioxide nanosheets and preparation method of water-based acrylic coating
CN115678365A
Resin composition
JP2003138145A
Polyolefin-Arylene-Ether Nanoplatelet Composites
US20190016885A1